Cancer stem cells and tumor transdifferentiation: implications for novel therapeutic strategies - Shekhani, Mohammed Talha (e-Century Publishing Corporation, 2013)
Highly malignant tumors mostly consist of rapidly proliferating cells. However, tumors also contain a few cells in a quiescent state that can be characterized as slow-cycling, expressing markers of stem cells and possessing the ability to initiate new tumors. These quiescent cells, now generally termed ‘cancer stem cells’ (CSC) (or ‘cancer initiating cells’), are capable of regenerating the entire tumor--as it occurs in metastatic spread. This process of tumor initiation by stem-like cells presumably involves differentiation of quiescent CSC into rapidly proliferating tumor cells. An important implication of the presence of slow cycling, quiescent stem-like cells in the tumor and their ability to initiate tumors is that they contribute to the resistance to treatments by conventional chemo- and radiotherapy directed toward killing rapidly dividing cells. However, similar to normal stem cells, the CSC could also potentially transdifferentiate into cell lineages other than the original lineage from which the tumor arose. Therefore, transdifferentiation of CSC offers a possible therapeutic strategy which has not yet been fully exploited. In this article, we provide a comprehensive review of the concepts in tumor cell transdifferentiation and discuss the mechanisms of transdifferentiation with emphasis on their relevance to potential novel treatment strategies.